Desempenho agronômico e acúmulo de nutrientes em melancia submetida à enxertia e adubação nitrogenada - Silva, Joyce Reis (2016)
The grafting on watermelon can be used as a management practice to improve the ability of the crops to absorb nitrogen and minimize the potential loss of this nutrient. This study aimed to evaluate the agronomic performance eacúmulo nutrient in watermelon grafted on to nitrogen fertilization. Two experiments were conducted in the years 2014 and 2015 in the Bebedouro Experimental Station, Embrapa Semi-Arid in Petrolina - PE. The experiments were conducted in a randomized block in split plot with four replications. The plots consisted of five doses of nitrogen (0, 40, 80, 120 and 160 kg ha-1), and the subplots, the four combinations of grafting, 1) Cultivar BRS Opara without grafting; 2) BRS Opara grafted onto Line A (Citrullus lanatus var.citroides); 3) 'BRS Opara' grafted in Hybrid A (C. lanatus var.citroides crossing); and 4) 'BRS Opara' grafted in Hybrid B (C. crossing lanatus var.citroides x C. lanatus var. lanatus). The experimental unit consisted of a row with ten plants spaced 3.0 m x 0.8 m and and as a useful area was considered the six central plants for productivity evaluation and fruit quality. In the first larval experiment the following characteristics were assessed: total, commercial production, the total number of commercial and fruits per plant, commercial fruit weight, the efficiency of nitrogen, soluble solids, titratable acidity, soluble solids / titratable acidity, thickness peel and pulp firmness. plants were collected in the period of flowering and harvest to quantify the dry matter and accumulation of macro and micronutrients. further analysis was conducted of production cost and profitability of the plant grafted and ungrafted. In cv watermelon cultivation BRS Opara 'under fertigation, mulching and agrotextil mango grafting provided a more efficient absorption of nutrients in relation to non-grafted, reversing this productivity and improve the quality of fruit, grafting on Line A promoted increased productivity (60.8 t ha-1) at a dose 69.8 kg ha-1 N and commercial production (51.5 t ha-1) at a dose 69.3 kg ha-1 N is unrated reduction 48.4% in nitrogen fertilization and increase in net revenue of 39.8%